Desenvolvimento de pipeline para análise de amplicons - Bini, Aline Mara Rudsit (2021)
The application of computational tools in the field of molecular biology began in the last century, however it was in the 21st century that its high momentum came about. This is mainly due to the increase in data available for analysis, coming from the New Generation Sequencing (NGS), which made genomic sequencing cheaper and more efficient. In 2011, the annual global sequencing capacity reached 13 quadrillion nitrogen bases. Amid so much data generated, it is necessary to develop technological applications to extract useful information to be applied in research. In this work, a pipeline was developed to analyze amplicons based on an existing project. The code was refactored in order to make it scalable and portable, thus contributing to the bioinformatics community. For this, modern and well-respected tools were used to manipulate the pipeline, containerization, versioning and sharing: Nextflow, Docker and GitHub.